2007
DOI: 10.3727/096368907783338217
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Assistance by Grafting a New Bioartificial Upgraded Myocardium (MAGNUM Clinical Trial): One Year Follow-Up

Abstract: Cell transplantation for the regeneration of ischemic myocardium is limited by poor graft viability and low cell retention. In ischemic cardiomyopathy the extracellular matrix is deeply altered; therefore, it could be important to associate a procedure aiming at regenerating myocardial cells and restoring the extracellular matrix function. We evaluated intrainfarct cell therapy associated with a cell-seeded collagen scaffold grafted onto infarcted ventricles. In 15 patients (aged 54.2 +/- 3.8 years) presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 32 publications
0
84
0
1
Order By: Relevance
“…Direct injection of cells into the infracted myocardium has resulted in limited survival and retention of the transplanted cells [5,6]. Transplant survival has been increased with the induction of angiogenesis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Direct injection of cells into the infracted myocardium has resulted in limited survival and retention of the transplanted cells [5,6]. Transplant survival has been increased with the induction of angiogenesis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Presently one cardiac tissue engineering clinical trial has been completed using autologous bone marrow derived cells incorporated into a collagen sponge scaffold (Chachques et al, 2008). The clinical study recipients showed improvements at the one-year follow-up; however further studies are necessary to rule out confounding factors such as concomitant coronary artery bypass graft surgery (Chachques et al, 2007).…”
Section: -Cardiac Tissue Engineeringmentioning
confidence: 99%
“…33 Recently, a similar approach was used successfully in a clinical trial (MAGNUM trial) with a bone marrow mesenchymal stem cell-seeded collagen sponge applied on top of the scarred area, with the aim of regenerating myocardial cells and restoring extracellular matrix function which is deeply altered following myocardial infarction. 54,55 The MAGNUM trial is an example of the possible association between stem cell therapy and tissue engineering. Polymeric biomaterials have also been engrafted with growth factors, cytokines, and drugs, thus obtaining drug-releasing systems capable of focused and localized delivery of molecules, depending on the environmental requirements and the actual milieu in which the scaffold is placed.…”
Section: Tissue-engineered Predifferentiated Cellsmentioning
confidence: 99%